Relapse risk and survival in patients with FLT3 mutated acute myeloid leukemia undergoing stem cell transplantation. Issue 4 (13th February 2017) - Gaballa, Sameh; Saliba, Rima; Oran, Betul; Brammer, Jonathan E.; Chen, Julianne; Rondon, Gabriela; Alousi, Amin M.; Kebriaei, Partow; Marin, David; Popat, Uday R.; Andersson, Borje S.; Shpall, Elizabeth J.; et al.
Abstract: In patients with AML with FMS‐like tyrosine kinase 3 ( FLT3 ) mutations, the significance of minimal residual disease (MRD) detected by PCR before allogeneic stem cell transplantation (SCT) on outcomes after transplant remains unclear. We identified 200 patients with FLT3 ‐AML who underwent SCT at our institution. Disease status at transplant was: first or second complete remission (CR1/CR2, n  = 119), high‐risk CR (third or subsequent CR, marrow hypoplasia, or incomplete count recovery) (CR‐HR, n  = 31), and morphological evidence of active disease (AD, n  = 50). The median follow‐up was 27 months, and the 2‐year overall and progression‐free survival were 43% and 41%, respectively. Relapse was highest in the AD group (85%) and the CR‐HR FLT3 MRD positive group (72%), followed by CR‐HR FLT3 MRD negative (58%), CR1/CR2 FLT3 MRD positive (39%), and lowest in the CR1/CR2 FLT3 MRD negative group (23%). On multivariate analysis, independent factors influencing the risk of relapse were detectable morphological disease and FLT3 MRD by PCR pre‐transplant. Factors that did not influence the relapse risk included: age, graft type, graft source, type of FLT3 mutation, or conditioning intensity. Morphologic and molecular remission status at the time of transplant were key predictors of disease relapse and survival in patients with FLT3 ‐AML.